دور القيادة التحويلية في تحسين مستوى الروح المعنوية للعاملين (دراسة مسحية على العاملين ضمن المصارف العاملة في محافظة اللاذقية) - عمار, قصي; سليمان, أنس (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تناول هذا البحث دور القيادة التحويلية في تحسين مستوى الروح المعنوية للعاملين، من خلال دراسة مسحية على العاملين ضمن المصارف العاملة في محافظة اللاذقية. يتمثل الهدف الرئيسي للبحث في دراسة أبعاد القيادة التحويلية، والتعرف على مستوى الروح المعنوية السائدة بين العاملين في المصارف المدروسة، ودراسة العلاقة بين القيادة التحويلية وتحسن مستوى الروح المعنوية لدى العاملين في المصارف المدروسة.وكانت عينة البحث (276) مفردة، وقد تم الاعتماد على مقياس القيادة متعددة العوامل (MLQ Form X5) لقياس القيادة التحويلية، وعلى مقياسي (Linz et al,2006) و(الخالدي،2008) لقياس الروح المعنوية، وبلغ معامل الثبات ألفا كرونباخ للاستبيان المعد ككل (96.6%)، وبالاعتماد على الإحصاءات الوصفية (المتوسطات والانحرافات المعيارية)، و اختبار ( t ) لعينة واحدة، واختبار الانحدار الخطي المتعدد. توصل الباحث إلى النتائج الأتية: _ إن القيادات الإدارية في المصارف المدروسة تمارس القيادة التحويلية._ إن مستوى الروح المعنوية مرتفع إلى حد ما في المصارف المدروسة._ توجد علاقة إيجابية معنوية بين ممارسة القيادة التحويلية ومستوى الروح المعنوية في المصارف المدروسة._ توجد علاقة إيجابية معنوية بين التأثير المثالي ومستوى الروح المعنوية في المصارف المدروسة._ توجد علاقة إيجابية معنوية بين التشجيع الابداعي ومستوى الروح المعنوية في المصارف المدروسة._ توجد علاقة إيجابية معنوية بين التحفيز الإلهامي ومستوى الروح المعنوية في المصارف المدروسة._ توجد علاقة إيجابية معنوية بين الاهتمام الفردي ومستوى الروح المعنوية في المصارف المدروسة.This study examined the role of transformational leadership in improving the morale of the employees, through a survey study on employees in Latakia banks. This study aimed to examine transformational leadership dimensions, Identify the level of morale employees in the studied banks, and the study of the relationship between transformational leadership and improve the level of morale among workers in the studied banks. The research sample (276) Single, has been relying on multiple factors driving scale (MLQ Form X5) for measuring transformational leadership, and the Standart (Linz et al, 2006) and (Khalidi, 2008) to measure morale, and reached stability alfa Cronbach questionnaire coefficient prepared a whole (96.6%), and based on descriptive statistics (averages and standard deviations),( t ) test for one sample, And testing of multiple linear regression, and the researcher concluded to the following results:_ The administrative leaders in the study of banks practicing transformational leadership._ The level of morale is fairly high in the studied banks. _ There is a positive relationship significant differences between the practice of transformational leadership and the level of morale in the studied banks._ There is a positive relationship significant differences between the idealize influence the level of morale in the studied banks._ There is a positive relationship significant differences between the encouragement of creativity and the level of morale in the studied banks._ There were significant positive correlation between moral motivation and inspirational level of morale in the studied banks._ There is a positive relationship significant differences between individual attention and the level of morale in the studied banks.